ASPEK HUKUM ARISAN STUDI TERHADAP PELAKSANAAN ARISAN PADA KELOMPOK DAGING DI KELURAHAN RONTU KOTA BIMA - Ahmad; Angga Paramita; Dati Amaliyah (Bajang Institute, 2021)
Group social gathering activities in the community are now institutionalized as a habit to help each other among others on the basis of mutual trust. The purpose of this study is to try to uncover the legal arrangements for the social gathering and the legal consequences that occur when the arisan member defaults. The research method used is empirical legal research with a sociological approach. The results of the study show that arisan activities have not been legally regulated, while in the event of a default, they can be subject to forced collection and criminal charges of embezzlement.